1993
DOI: 10.1017/s0963548300000547
|View full text |Cite
|
Sign up to set email alerts
|

Upper Bounds for the Connective Constant of Self-Avoiding Walks

Abstract: We present a method for obtaining upper bounds for the connective constant of self-avoiding walks. The method works for a large class of lattices, including all that have been studied in connection with self-avoiding walks. The bound is obtained as the largest eigenvalue of a certain matrix. Numerical application of the method has given improved bounds for all lattices studied, e.g. μ < 2.696 for the square lattice, μ < 4.278 for the triangular lattice and μ < 4.756 for the simple cubic lattice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 22 publications
0
56
1
Order By: Relevance
“…These bounds are sharper than the one obtained by Alm [2], µ tri < 4.277799, using n = 16 and m = 6 (Alm has since improved this to µ tri < 4.25152 [3]). For the hexagonal lattice we have c 100 = 2585241775338665938539885252 and c 99 = 1394474897269109512317080364, which gives us the upper bounds µ 1 = 1.871004, µ 2 = 1.869731 and µ a = 1.869836.…”
Section: Upper Boundsmentioning
confidence: 88%
See 1 more Smart Citation
“…These bounds are sharper than the one obtained by Alm [2], µ tri < 4.277799, using n = 16 and m = 6 (Alm has since improved this to µ tri < 4.25152 [3]). For the hexagonal lattice we have c 100 = 2585241775338665938539885252 and c 99 = 1394474897269109512317080364, which gives us the upper bounds µ 1 = 1.871004, µ 2 = 1.869731 and µ a = 1.869836.…”
Section: Upper Boundsmentioning
confidence: 88%
“…The best current method for obtaining upper bounds is due to Alm [2] and it essentially requires one to enumerate the number of walks according to length n and a specified head and tail each of length m. More precisely Alm showed that…”
Section: Upper Boundsmentioning
confidence: 99%
“…For the square lattice it has been shown rigorously that c ‫ޚ‬ 2 ≤ 2.7 (see [1]), which implies that we have no infinite self-avoiding path with bounded partial sums for p ∈ [0, 0.035) ∪ (0.965, 1].…”
Section: Theoremmentioning
confidence: 99%
“…But it is rigorously known that µ 2 ≤ 2.69576, µ 3 ≤ 4.756, µ 4 ≤ 6.832 [1], and it is expected that µ 2 = 2.638, µ 3 = 4.683, µ 4 = 6.775 [18]. The numerical values using Corollary 1 and the above upper bounds and expected values of µ ν are listed in the Table, and they are in good agreement with experimental results except for two dimensional cases.…”
Section: Lemma 2 the Representationsmentioning
confidence: 99%